Characteristics of macrophage-like cells in acute nonarteritic anterior ischemic optic neuropathy and the normal fellow eyes on en face optical coherence tomography - Wang, Wenyu; Chen, Changzheng; Yi, Zuohuizi; Wang, Xiaoling; Luo, Huijuan (Frontiers in Immunology, 2022)
URPOSE: To quantitatively analyze macrophage-like cells (MLCs) at the vitreoretinal interface (VRI) in acute nonarteritic anterior ischemic optic neuropathy (NAION) using en face swept-source optical coherence tomography (OCT). METHODS: Twenty-five acute NAION eyes and 25 normal fellow eyes from 25 patients were included in the study. MLCs were visualized in a 3 μm 6 mm×6 mm en face OCT slab above the VRI centered on the optic nerve head (ONH). After semiautomatic binarization and quantification, we evaluated the MLC density between the two groups. We also investigated the relationship between MLC density and other OCT parameters, including the increase in peripapillary retinal nerve fiber layer (RNFL) thickness and loss of vessel density (VD) in radical peripapillary capillary (RPC). RESULTS: The MLC density in the affected eye of the ONH was highly correlated with that in the fellow eye (r=0.612, p=0.001). The MLC density significantly increased in acute NAION eyes (NAION vs. normal, 11.97±6.66 vs. 9.31±6.10 cell/mm2, p=0.028). In sectorial analysis, the increase in MLCs was mainly in the superior regions (4.13±7.49 vs. 0.94±5.21 cell/mm2, p=0.001). The VD of RPC decreased significantly in the affected eyes (NAION vs. normal, 37.54±5.25 vs. 40.56±4.25, p=0.016), and the loss of RPC was predominantly in the superior sectors and the temporal sectors when compared to the inferior sectors and the nasal sectors, respectively (superior vs. inferior, -3.54±6.71 vs. -0.37±8.07, p=0.004; temporal vs. nasal, -2.69±8.72 vs. -1.22±6.06, p=0.005). The loss of RPC and the increase in MLC density were greater in affected sector corresponding to the visual field (VF) defect. CONCLUSION: MLCs located above the VRI increased significantly in acute NAION eyes，especially in subregions corresponding to VF defect, which provides clinical evidence supporting that the inflammatory response participates in the pathological process of NAION. The magnitude of the increase in MLCs corresponds to the RPC loss in the quadrant analysis.